Beyond individual barriers and facilitators: Digital interventions to address diabetes in urban Ghana - Ethan Gray; Ann Blandford; Samuel Amon; Publa Antwi; Vida Asah-Ayeh; Raphael Baffour Awuah; Leonard Baatiema; Sandra Boatemaa Kushitor; Hassan Haghparast-Bidgoli; Hannah Maria Jennings; Irene Akwo Kretchy; Daniel Strachan; et al. (Digital Health, 2025)
Objective The prevalence of type 2 diabetes (T2D) and other non-communicable diseases (NCDs) in Ghana and other countries in sub-Saharan Africa (SSA) is increasing at a rate notably higher than the rest of the world. Consequently, there is an urgent need to develop low-cost community interventions for diseases including T2D in Ghana, with digital tools potentially empowering community members in prevention and management. This research aimed to identify effective strategies for leveraging digital tools to address T2D in Ga Mashie, Ghana, through community-driven empowerment and action. Method This was a mixed methods study involving focus groups (N = 13), qualitative interviews with community representatives (N = 69) and two community workshops (N = 35 participants in each). Results The focus groups and interviews identified strong facilitators for an individual-level digital intervention focused on education; however, workshops highlighted that the community wants greater access to in-person education and healthcare services in Ga Mashie, limiting the likely impact of an individual digital intervention. Conclusion Our findings challenge the widespread assumption that digital interventions should be targeted at the individual; rather, digital tools might be used to empower community leaders in Ga Mashie with training and clinical guidance to function as healthcare agents, scaling-up the delivery of education and screening services to their broader community. This suggests a novel system-level strategy for designing community-based, empowerment-focused digital health interventions that reflect the practices and values of community members, though further work is needed to validate this approach.